2013
DOI: 10.1039/c3cp44451a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering electrodeposited ZnO films and their memristive switching performance

Abstract: We report the influence of zinc oxide (ZnO) seed layers on the performance of ZnO-based memristive devices fabricated using an electrodeposition approach. The memristive element is based on a sandwich structure using Ag and Pt electrodes. The ZnO seed layer is employed to tune the morphology of the electrodeposited ZnO films in order to increase the grain boundary density as well as construct highly ordered arrangements of grain boundaries. Additionally, the seed layer also assists in optimizing the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 55 publications
(64 reference statements)
1
39
0
Order By: Relevance
“…Therefore, set and reset voltages in ECM are lower than that in VCM. Nevertheless, it is reported that a high electronegativity of Au may also behave as active metals [ 108 ]; in addition, the omission of Ni or Ag atoms diffusion in CF formation is also reported [ 166 , 167 ]; this phenomena may relate to different ZnO film quality, device geometry, and operation method. The major device parameters as a function of different metal electrodes are summarized in Table 1 .…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, set and reset voltages in ECM are lower than that in VCM. Nevertheless, it is reported that a high electronegativity of Au may also behave as active metals [ 108 ]; in addition, the omission of Ni or Ag atoms diffusion in CF formation is also reported [ 166 , 167 ]; this phenomena may relate to different ZnO film quality, device geometry, and operation method. The major device parameters as a function of different metal electrodes are summarized in Table 1 .…”
Section: Reviewmentioning
confidence: 99%
“…Since then, the fabrication and study of memristive devices have become very popular due to their applications in information storage, non-volatile memories, neural networks, etc. [3-5] Memristive switching behavior has been observed in many metal oxides [6,7] and attributed to the migration of oxygen vacancies within the oxide layers and grain boundaries [8,9], but still, transport mechanisms are being studied and different models have been suggested [7-9]. Zinc oxide (ZnO) possesses several interesting properties and has been extensively studied for its technological applications, specifically in electronic and optoelectronic devices such as photodetectors [10,11], light-emitting diodes [12], solar cells [13,14], and gas sensing [15].…”
Section: Introductionmentioning
confidence: 99%
“…A seed layer is therefore essential in order to achieve well aligned nanorods on the substrate. Recently, several seed coating techniques have been used for the growth of well-ordered ZnO nanorods, such as atomic layer deposition (ALD), pulsed laser deposition (PLD) [18], electron beam evaporation (EBE) [19], the successive ionic layer adsorption and reaction (SILAR) method [20], spray pyrolysis [21], and RF sputtering techniques [22,23]. The growth of ZnO nanorods, homogeneously perpendicular to the substrate, is a challenging task using a simple and low temperature aqueous chemical growth method.…”
Section: Introductionmentioning
confidence: 99%